Financial Literacy and Inclusion in Indonesia During the Crisis: A Content Analysis Approach - Dunggio, Maryam; Chusnah (Faculty of Economics and Business, Universitas Negeri Yogyakarta in collaboration with the Institute for, 2025)
This study aims to identify and describe the condition of financial literacy and inclusion in Indonesia during the covid-19 pandemic crisis (March 2, 2020 – August 31, 2022). The data used are news published in online news media, namely Kompas.id. The number of news articles used was 65. The analysis method used is content analysis. The result of this study’s analysis show that the main topic that is most discussed about financial literacy and inclusion in Indonesia is the poor condition of financial literacy and inclusion in Indonesia. The most discussed special topic about financial literacy is the community group that is the focus of financial literacy. Meanwhile, low financial literacy is the most discussed sub-topic. Efforts to increase financial inclusion are the topic with the highest frequency of discussion related to financial inclusion in Indonesia. The most discussed sub-topic related to financial inclusion is digital-based financial inclusion.